Cerebral Blood Flow–Guided Manipulation of Arterial Blood Pressure Attenuates Hippocampal Apoptosis After Asphyxia‐Induced Cardiac Arrest in Rats. Issue 13 (7th July 2020) - Wang, Chih‐Hung; Chang, Wei‐Tien; Huang, Chien‐Hua; Tsai, Min‐Shan; Liu, Shing‐Hwa; Chen, Wen‐Jone
Abstract : Background: In most post–cardiac arrest patients, the autoregulation mechanism of cerebral blood flow (CBF) is dysregulated. We examined whether recovery of CBF by adjusting mean arterial pressure mitigates post–cardiac arrest neuronal damage. Methods and Results: Wistar rats that underwent 8‐minute asphyxia‐induced cardiac arrest and resuscitation were computer‐randomized to norepinephrine or control groups. The CBF was measured at the dorsal hippocampal CA1 region of the left hemisphere. In the norepinephrine group, the mean arterial pressure was adjusted to recover CBF to 80% to 100% of baseline. Twenty‐four hours following resuscitation, neurological outcomes were assessed, and brain tissues and blood samples were harvested for neuronal apoptosis and injury assessment. Thirty resuscitated rats were randomized into 2 groups, each containing 12 rats that completed the experiments. Norepinephrine infusion effectively prevented posthyperemia hypoperfusion and recovered CBF to pre‐arrest baseline levels; a moderate positive linear correlation between mean arterial pressure and CBF during this period was also observed ( P <0.001). There were no significant between‐group differences in neurological recovery. In the norepinephrine group compared with the control group, upregulated cleaved caspase‐3 protein expression in brain tissue determined by Western blot was reduced ( P =0.02) and the densities of apoptotic cells in hippocampal CA1 and CA3 regions determined by terminal deoxynucleotidyl transferase‐mediated dUTP biotin nick‐end labeling were decreased ( P <0.001). No significant differences in serum neuron‐specific enolase or S100β levels were detected between the 2 groups. Conclusions: CBF recovery demonstrated neuroprotective effects by reducing activation of cerebral apoptosis and number of apoptotic neurons. However, these effects did not significantly improve clinical neurological function, necessitating further investigation.